Development of antibody prodrug conjugates activated by legumain - Lerchen, Hans-Georg (Henry Stewart Talks, 2021)
Modular composition of antibody drug conjugates, ADC mode of action, TWEAK receptor as an ADC target, Improvements to achieve stable antibody conjugation, KSP inhibitors as ADC toxophores, Legumain-cleavable antibody prodrug conjugates, Conceptualization of Antibody Prodrug Conjugates (APDCs) to increase the therapeutic window